Relationship between the sensation of activity limitation and the results of functional assessment in asthma patients. (3rd July 2017) - Vermeulen, Francois; Chirumberro, Audrey; Rummens, Peter; Bruyneel, Marie; Ninane, Vincent
ABSTRACT: Objective : In asthma patients, the assessment of activity limitation is based on questions evaluating how limited the patient feels in their activities. However, the lack of functional data complicates the interpretation of the answers. We aimed to evaluate the intensity of relationships between the patient's perception of activity limitation and the results of several functional tests. Methods : Twenty patients complaining of asthma exacerbation were invited to complete three scores (Chronic Respiratory Disease questionnaire, Asthma Control Questionnaire, Hospital Anxiety and Depression scale). They also underwent lung function measurements, a 6-minute walk test and a cardio-pulmonary exercise test. In addition, physical activity was studied by actigraphy. Spearman's rank correlation coefficients between the patient's perception of activity limitation and each of the other parameters were analysed. Results : Five parameters were significantly correlated with the perception of activity limitation: ACQ question 4, related to dyspnea (rs 0.74, p < 0.001); Emotion domain of the Chronic Respiratory Disease questionnaire (rs −0.57, p = 0.02); HAD anxiety (rs 0.48, p = 0.032); HAD depression (rs 0.46, p = 0.041); ACQ question 6, related to reliever use (rs 0.46, p = 0.046). No parameters from the lung function test, 6MWT, CPET or actigraphy, were significantly correlated with the perception of activity limitation. Conclusions : In response to questions about limitation of activity, patients do not specifically answer mentioning physical limitation but rather the psychological burden associated with this constraint.